2011
DOI: 10.1126/scitranslmed.3001069
|View full text |Cite
|
Sign up to set email alerts
|

A MEK Inhibitor Abrogates Myeloproliferative Disease in Kras Mutant Mice

Abstract: Chronic and juvenile myelomonocytic leukemias (CMML and JMML) are aggressive myeloproliferative neoplasms that are incurable with conventional chemotherapy. Mutations that deregulate Ras signaling play a central pathogenic role in both disorders, and Mx1-Cre, KrasLSL-G12D mice that express the Kras oncogene develop a fatal disease that closely mimics these two leukemias in humans. Activated Ras controls multiple downstream effectors, but the specific pathways that mediate the leukemogenic effects of hyperactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
86
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 28 publications
7
86
0
Order By: Relevance
“…This was unexpected, as the MEK inhibitor from which PD0325901 was derived failed to show efficacy in a GEM model of Nf1 JMML (53). Recently, PD0325901 was found to be effective in reversing myeloproliferative disease in an activated KRas mouse model (54) and in Nf1-driven JMML (33), likely due to the more persistent inhibition of MEK by PD0325901, a second-generation MEK inhibitor modified to improve efficacy for clinical cancer trials (55). Collectively, these studies suggest that Raf/MEK/ERK is a critical pathway in NF1.…”
Section: Discussionmentioning
confidence: 99%
“…This was unexpected, as the MEK inhibitor from which PD0325901 was derived failed to show efficacy in a GEM model of Nf1 JMML (53). Recently, PD0325901 was found to be effective in reversing myeloproliferative disease in an activated KRas mouse model (54) and in Nf1-driven JMML (33), likely due to the more persistent inhibition of MEK by PD0325901, a second-generation MEK inhibitor modified to improve efficacy for clinical cancer trials (55). Collectively, these studies suggest that Raf/MEK/ERK is a critical pathway in NF1.…”
Section: Discussionmentioning
confidence: 99%
“…Selective inhibition of MEK abrogated the myeloproliferative disease in Nf-1 and Kras mutant mice 103,104 suggesting that MEK inhibitors might ameliorate hematologic abnormalities in JMML. Although therapeutic windows for pan inhibitors of the MAPK pathway may be limited,1 early clinical studies in JMML are needed to gain more insight into the specific signaling network of this rare disease.…”
Section: Treatment Other Than Stem Cell Transplantationmentioning
confidence: 99%
“…30,55,56 Previous work has demonstrated that MEK inhibition can attenuate myeloid neoplasia but is insufficient to cure this disease in either mouse models or human patients. 23,[56][57][58] Kras G12D myeloid cells remain hypersensitive to cytokines (according to colonyforming assays) despite MEK inhibition. 23 Jak inhibition abrogates GM-CSF-dependent ERK phosphorylation in Kras G12D myeloid cells.…”
Section: Discussionmentioning
confidence: 99%
“…23,[56][57][58] Kras G12D myeloid cells remain hypersensitive to cytokines (according to colonyforming assays) despite MEK inhibition. 23 Jak inhibition abrogates GM-CSF-dependent ERK phosphorylation in Kras G12D myeloid cells. 59 These results indicate that other pathways contribute to disease in leukemias with hyperactive RAS signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation